Melkersson-Rosenthal Syndrome: A Review of Clinical Presentation, Diagnosis and Management - Megha Tidke; Pramod Borghare; Piyush Pardhekar; Raza Salim Sheikh (Journal of Clinical and Diagnostic Research)
Melkersson-Rosenthal Syndrome (MRS) is a rare neuro-mucocutaneous disorder characterised by a triad of recurrent facial palsy, orofacial swelling and fissured tongue. The complete triad occurs in fewer than 25% of cases, complicating timely diagnosis and management. The present review focuses on the clinical features, diagnostic difficulties and management approaches of MRS, hence establishing its clinical relevance and treatment results. A literature survey is conducted based on case reports, clinical trials and MRS reviews. The approach towards the diagnosis and different modes of treatments with multidisciplinary management analysis, is done. MRS is a condition with some diagnostic difficulties because it often presents variably and even mimics other diseases like angioedema, Bell’s palsy and Crohn’s disease. The gold standard of histopathology is the presence of non caseating granulomas. The acute symptoms can be treated with corticosteroids, as early as 30 to 60 mg/day; however, long-term treatment has to be avoided because of complications such as osteoporosis. Immunocompressants, like methotrexate and azathioprine, are used in refractory cases. Some of the considerations and measures would be surgical interventions, cheiloplasty and nerve decompression. However, these are risky to be accompanied by scarring, nerve damage, recurrence of symptoms and so on. A multidisciplinary approach involving dermatologists, neurologists and psychologists is critical for improving patient outcomes and quality of life. In conclusion, MRS remains a diagnostic and therapeutic challenge because of its persistence and various presentations. Accurate and early diagnosis, immediate intervention and a multidisciplinary approach to treatment will be necessary to prevent complications. Future studies on the genetic and immunological basis of MRS will help develop better diagnostic and therapeutic options.